Racialising French Practices of Secularism (Laïcité): A Portrait of the ‘Cyber-Abuse’ of Muslim and Islamic Attributes on Twitter Platforms in 2023 - Rifqi, Naflah; Manggala, Kayan; Kholil, Ahmad (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2024)
This study is motivated by the ongoing debates surrounding France and Islam over the past decade, particularly the re-emergence of laïcité as a historical ideology rooted in the late 18th century. The research aims to examine how French citizens express their perspectives on issues related to Islam, Islamofobia, and Muslim identity through narratives on Twitter, and to analyze how the racialization and marginalization of laïcité are perceived comprehensively. Using tweet harvesting for data collection and analysis facilitated by MAXQDA, the study identifies key events in 2023 that sparked public discourse: the ban on the abaya in schools and the celebration of Hanukkah at the Presidential Palace. Analysis of tweet content reveals three primary groups of public opinion: feminists (notably in the context of the abaya), nationalists who advocate for laïcité, and neutral humanists who, while often critical, also challenge the racialization of political actions. In addition to the frequent use of offensive language and calls for the exclusion of Muslims opposing government policies, secondary sources indicate tangible forms of racialization in society. These findings highlight that many view the Muslim population as outsiders, despite being born and raised in France.